Deviation and mobility in female characters stimulated through ‘structure of feeling’ in selected American novels - Fejer, Azhar Noori (2015)
The publication of John Updike’s The Witches of Eastwick (1984) made the author subject to much attacks and hostility. Feminists saw the book to be greatly offensive towards modern women. The three witches in the novel are depicted as carefree, malicious and murderers. Actually, this modern image of women varies significantly from the traditional ‘True Woman’ image that was predominant in American culture for a quite long time. This thesis traces the development in the female character in the works of four selected American authors between the years 1850s – 1980. The female characters were not notable before the 1850s. Generally, the predominant images were the good and the bad; hence, the American female character remained a stereotype. A steady deviation happened in the depiction of this character; the old, feeble, subordinate, passive woman was substituted with a strong, dominant, and sometimes daring figure. The study reveals that the deviation in the depiction of the female character is due to the ‘new structure of feeling’ that particular American authors possessed. These authors were influenced by different changes in life as a whole. In this study, I use a cultural materialist approach in which I return the literary texts to their historical context, and show the political commitments of the period. I also show the different genres and techniques the authors employ in order to come out with a developed female character. The textual analysis is based on social feminism approach since cultural materialist analysis often has political agendas. In my exploration of the stages of the female character’s development in American fiction, I focus on Raymond Williams’ concept of ‘structure of feeling’ to show the new sense of life these authors had attained that stimulated them to make an obvious ‘deviation’ during the second half of the nineteenth-century. I also display how this continuous deviation has led to the presentation of ‘individual mobility’ within the turn of the twentieth-century, and to ‘social mobility’ in the second half of the century. In my exploration of the deviation and the development in the female character, I focus on Nathaniel Hawthorne’s The Scarlet Letter (1848), and Harriet Wilson’s Our Nig, (1859). Sylvia Plath’s The Bell Jar (1963) exemplifies ‘individual mobility’, and, the final stage is going to be with John Updike’s The Witches of Eastwick (1984) which represents ‘social mobility,’ and the modern female image. The four authors were evoked by their ‘structure of feeling’, wished to present certain characteristics of women that were overshadowed by American patriarchal society.